KAJIAN ETNOPEDAGOGI TERHADAP YOGA SEBAGAI TRADISI BALI - Tristaningrat, Made Adi Nugraha (Institut Hindu Dharma Negeri Denpasar, 2018)
Teaching yoga is not a teaching which is concerned specifically about the teachings of a particular religion or belief. Yoga literally comes from the word ?yuj? which means uniting or connecting with God. Yoga is basically a means or way of life, not something out of life, is not it also distanced itself from the activities, but rather is an efficient performance by the true spirit of life. Yoga nor run away from home and habits of human life, but instead is a process of the formation of attitude to life at home (family) as well as social life with order and tradition that followed included also in the scope of Balinese tradition in particular. Yoga in the tradition of Bali are reflected in all the viable commonplace example done in Yoga known there is a term which is a type of yoga Asanas in terms of movement both in the standing position, sitting, and lying down. Asanas indirectly has done in a civic order Bali through sitting cross-legged when visited, lined up neatly, to carry out the process of worship that uses or standing cross-legged stance. This behavior does not necessarily constitute the heritage of our Yoga Science adoption directly or indirectly in everyday life, but it is an idea that something that reflects the local wisdom has the feel a clear education as a meaningful review.